Travel burden associated with granulocyte colony-stimulating factor administration in a Medicare aged population: a geospatial analysis. (3rd August 2018) - Stephens, J. Mark; Bensink, Mark; Bowers, Charles; Hollenbeak, Christopher S.
Abstract: Objective: Prophylaxis with granulocyte colony-stimulating factors (G-CSFs) is recommended for patients receiving myelosuppressive chemotherapy regimens with a high risk of febrile neutropenia (FN). G-CSFs should be administered starting the day after chemotherapy, necessitating return trips to the oncology clinic at the end of each cycle. We examined the travel burden related to prophylactic G-CSF injections after chemotherapy in the US. Methods: We used 2012–2014 Medicare claims data to identify a national cohort of beneficiaries age 65+ with non-myeloid cancers who received both chemotherapy and prophylactic G-CSFs. Patient travel origin was based on residence ZIP code. Oncologist practice locations and hospital addresses were obtained from the Medicare Physician Compare and Hospital Compare websites and geocoded using the Google Maps Application Programming Interface (API). Driving distance and time to the care site from each patient ZIP code tabulation area (ZCTA) were calculated using Open Street Maps road networks. Geographic and socio-economic characteristics of each ZCTA from the US Census Bureau's American Community Survey were used to stratify and analyze travel estimates. Results: The mean one-way driving distance to the G-CSF provider was 23.8 (SD 30.1) miles and the mean one-way driving time was 33.3 (SD 37.8) minutes. When stratified by population density, the mean one-way travel time varied from 12.1 (SD 10.1) minutes in Very Dense Urban areas to 76.7 (SD 72.1) minutes in Super Rural areas. About 48% of patients had one-way travel times of <20 minutes, but 19% of patients traveled ≥50 minutes one way for G-CSF prophylaxis. Patients in areas with above average concentrations of aged, poor or disabled residents were more likely to experience longer travel. Conclusions: Administration of G-CSF therapy after chemotherapy can present a significant travel burden for cancer patients. Technological improvements in the form and methods of drug delivery for G-CSFs might significantly reduce this travel burden.